2020
DOI: 10.3390/cancers12071917
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Non-Informative Circulating Tumor DNA to Monitor the Mutational Landscape in NSCLC

Abstract: In non-small cell lung cancer (NSCLC) the usage of plasma-derived circulating tumor DNA (ctDNA) have come into focus to obtain a comprehensive genetic profile of a given lung cancer. Despite the usage of specific sampling tubes, archived plasma samples as well as inappropriately treated blood samples still cause a loss of information due to cell lysis and contamination with cellular DNA. Our aim was to establish a reliable protocol to rescue ctDNA from such non-informative samples to monitor the mutational lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The range has been reported to be between 10 and 1000 ng/µL in some studies [17], while others have shown it to be between 0.1 and 12 ng/µL. Similarly, the ctDNA concentration in healthy donors has also varied in past studies, ranging from 0 to 100 ng/µL [18]. It is important to note that comparing results from different studies can be challenging due to differences in sample size, patient populations, and detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…The range has been reported to be between 10 and 1000 ng/µL in some studies [17], while others have shown it to be between 0.1 and 12 ng/µL. Similarly, the ctDNA concentration in healthy donors has also varied in past studies, ranging from 0 to 100 ng/µL [18]. It is important to note that comparing results from different studies can be challenging due to differences in sample size, patient populations, and detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the testing process requires sophisticated laboratory equipment, highly trained medical personnel, and prolonged processing time (days, even weeks). These limitations have led to skepticism regarding the clinical utility of this technology 64 .…”
Section: Ultra-sensitive Sensor and Multiplex Analysis For Dynamic Ch...mentioning
confidence: 99%
“…The complexity of the testing process requires sophisticated laboratory equipment, highly trained medical personnel, and prolonged processing time (days, even weeks). These limitations have led to skepticism regarding the clinical utility of this technology 64 .…”
Section: Ultra-sensitive Sensor and Multiplex Analysis For Dynamic Ch...mentioning
confidence: 99%